The development of Islamic finance in Malaysia - Md Nor, Mohd Zakhiri; Mohamad, Ani Munirah; Yaacob, Hakimah (CLJ Publication, 2016)
The Islamic finance industry has gained popularity and captured the attention of people all over the world.Today, Malaysia appears to be one of the leading Islamic finance players in the world, since the passing of the first legislation of Islamic finance in 1983 i.e. the Islamic Banking Act 1983. The industry continues to progress until today, further promising robust development in the coming future.This chapter will discuss the development of the Islamic finance industry in Malaysia based on the three main sectors which are increasingly gaining popularity and visibility: banking and finance, takaful and securities